Elaboration–Fluency Cognitive Activation Theory of Creative Thinking in Mathematics Performance: Evidence from Structural Equation Modeling - Jackie V. Borres; Jay Fie P. Luzano (Future Science / FSH-PH Publications, 2026)
ive thinking is widely recognized as essential for mathematics learning; however, the structural mechanisms linking its domains to mathematics performance remain insufficiently understood. This theory-building study investigated the relationship between the domains of creative thinking and mathematics performance among junior high school learners. Using a quantitative, non-experimental design, data were collected from 300 Grade 9 learners in the Tugbok District, Division of Davao City, Philippines. Creative thinking was operationalized using a researcher-developed 16-item instrument that assessed four domains: fluency, flexibility, originality, and elaboration. The instrument is an open-ended questionnaire requiring respondents to generate varied responses, which were evaluated using teacher-scored rubrics. Fluency was measured by relevant ideas produced to solved the problems; flexibility by the diverse of solution of strategies used; originality by the uniqueness with valid reasoning of responses; and elaboration by the level of explanation, clarity of ideas, and completeness of mathematical steps used. Mathematics performance was obtained from official academic records. Structural Equation Modeling (SEM) was fit to utilize for testing multiple hypothesized models and identify which among the models is the best-fitting structural representation of these relationships. Results showed that elaboration do not significantly predict mathematics performance but indirectly significant when both the elaboration and mathematics performance is linked with fluency.